ANALISIS PENERIMAAN PENGGUNA TERHADAP ALGORITMA REKOMENDASI ARTIFICIAL INTELLIGENCE PADA SPOTIFY MENGGUNAKAN TAM - Dealy Alti; Valens Florencia; Kevin Fernando Cahyadi; Dicky Pratama (Jurnal Teknologi Informasi dan Komputer, 2026)
Artificial Intelligence (AI) has been transforming various sectors, and the music streaming industry is no exception. Spotify stands out for employing AI to deliver tailored music suggestions to its users. This research explores user responses to such AI-driven features by utilizing the Technology Acceptance Model as an analytical framework. The study evaluates four dimensions: perceived ease of use, perceived usefulness, behavioral intention, dan actual system use. A survey method was implemented, gathering responses from 100 Spotify users. The results were examined with the help of statistical tools, namely SPSS and SmartPLS. Findings reveal that users’ continued engagement is more strongly linked to the perceived advantages of AI recommendations than to how easy the system is to use.